INVESTASI DAN PEMILIHAN TEKNOLOGI PENGGILINGAN PADA AGROINDUSTRI PADI DENGAN PENDEKATAN FUZZY, STUDI KASUS DI KABUPATEN CIANJUR - Faqih Udin, Marimin, Sukardi, Agus Buono , Hariyadi Halid TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
For the Indonesian people, rice is a staple food that must be always available throughout the year. Therefore, the existence of rice agroindustry is vital and it needs to be developed continuously, so that it can support the increase of domestic rice production. The purposes of this research were to evaluate and select the appropriate rice milling technology that suitable to local condition, and to analyze of its investmentfeasibility. System approach was used in this research.A Fuzzy-AHP technique was used toevaluate its investment feasibility and to decide the technology appropriateness with special reference to Cianjur District. Research results show that the green technology was the most appropriate technology for developing rice agroindustry in Cianjur District, with score of 0.50, higher than scores of the integrated technology and the conventional technology with only reached values of 0.4 and 0.1, respectively. Furthermore, the result from fuzzy-investment analysis showed that an investment of Rp5.4 billion was required with NPV of Rp3.2 billion and IRR of 29.3%. These indicated that the investment of rice agroindustry was feasible.Keywords: rice, agroindustry of rice, fuzzy-AHP, fuzzy-investation